The impact of two different styles of presentation (linear and hierarchical) of the interactive digital tale on the development visual thinking skills - A field study on kindergarten in Al-Qaryat Governorate Saudi Arabia - - Ghzaly, Ayat Fawzy Ahmed (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying the impact of two different styles of presentations (linear and hierarchical) of the interactive digital tale on the development of the kindergarten children visual thinking skills. To achieve the purpose of the study, a list of visual thinking skills have prepared, achievement test for measuring those skills, and many stories have been designed and produced seeking for the development of visual thinking skills، The sample of the study consists of 75 children from the second stage in the kindergarten has been divided as follows, 25 children of the control group, 25 children of the first experimental group using (linear style), 25 children of the first experimental group using (hierarchical patterns). The descriptive method has been used in the study and analysis stage and the semi-experimental method in the experimental stage، The results of the research indicated that there are statistically significant differences at the level of 0.05 between the average scores of the first and second experimental group (linear and hierarchical presentation pattern in the interactive digital tale) and the control group in the post application of the achievement test of visual thinking skills in favor of the first and second experimental groups, there are no statistically significant differences between the scores of the first experimental group students (linear style) and the second (hierarchical style) in the post application on the achievement test of visual thinking skills، The researcher recommends paying attention to visual thinking in the different educational stages, and to employing and using stories Interactive (the tale) in kindergarten stages in developing visual thinking skills in particular.